Assessing Consumer Attention and Arousal Using Eye-Tracking Technology in Virtual Retail Environment - Kim, Nayeon; Lee, Hyunsoo (Frontiers in Psychology, 2021)
This study is aimed at investigating how consumers experience the retail environment visually, thus establishing a foundation for deeper insights into visual merchandising strategies. Specifically, we experimentally record and analyze consumers’ visual attention and emotional arousal in a test setting, and examine the influence of various elements as well as gender differences in recorded consumer responses. We conduct an experiment utilizing eye-tracking and virtual reality to analyze visual attention and emotional arousal in response to spatial and design elements in an immersive retail environment. We examine real-time measures of consumer interest and emotional responses during the retail experience. Valid gaze data from 24 male and 22 female participants are used for an analysis of total dwell time, total fixation count, and average pupil diameter. Consumers’ visual attention and emotional arousal showed different responses to specific areas of interest according to different spatial arrangements in the sales and service areas. This study statistically analyzed gender differences in consumer responses and performed a correlation analysis between visual attention and emotional arousal. Our findings provide insight into improving the design of retail environments for target consumers and contribute to building visual merchandising strategies.